DIPG-02. TRANSLATIONAL MR IMAGING CORRELATES FOR MOLECULAR ANALYSES IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (23rd April 2019) - Poussaint, Tina Young; Vajapeyam, Sridhar; Brown, Douglas; Kao, Pei-Chi; Ma, Clement; Greenspan, Lianne; Gupta, Nalin; Goumnerova, Liliana; Bandopadhayay, Pratiti; Beroukhim, Rameen; Ligon, Keith; Kieran, Mark; et al.
Abstract: PURPOSE: To correlate MR imaging findings with molecular analyses in DIPG. METHODS: Baseline MR imaging studies, including standard pre- and post-contrast MR sequences, were reviewed from patients included in our multi-institutional, IRB-approved DIPG trial NCT01182350. Prospectively acquired imaging data were analyzed after study closure, including FLAIR/T2 tumor volume; tumor volume enhancement and cyst/necrosis; median, mean, mode, skewness, and kurtosis of apparent diffusion coefficient (ADC) tumor volume based on both FLAIR and enhancement at baseline. Whole-genome and RNA-sequencing identified histone mutations. We applied univariate Cox proportional-hazards regression modeling to test the association of imaging predictors with overall (OS) and progression-free survival (PFS). Wilcoxon rank-sum, Kruskal-Wallis, and Fisher's exact tests compared imaging measures between groups. RESULTS: Fifty patients underwent biopsy and MRI. Median age at trial registration was 6 years (range, 3.3–17.5 years); 52% of patients were female. Molecular subgroup study assignments for 48 patients' tumors were as follows: 28 in MGMT-/EGFR-, 14 in MGMT-/EGFR+, 3 in MGMT+/EGFR-, and 3 in MGMT+/EGFR+. Further genetic testing identified mutations in histones, PDGFRA, ACVR1, TP53, EGFR, PPM1D, FGFR, and/or PI3K. Twenty-three tumors possessed histone mutations in H3F3A, 8 in HIST1H3B, and 3 in HISTH3C. Median follow-up time was 11 months (range, 0.4–33 months). Poorer OS (p=0.01) and PFS (p=0.001) were significantly associated with increased enhancing tumor volume. Enhancing tumor volume also differed significantly across molecular subgroups (p=0.047). Tumor enhancement, mode, skewness, and kurtosis ADC-FLAIR differed significantly (p≤0.048) between patients with H3F3A and HIST1H3B mutations. Tumor enhancement, median, mode, skewness, and kurtosis ADC-FLAIR also differed significantly (p≤0.048) between patients with H3F3A and HIST1H3B or HISTH3C mutations. CONCLUSIONS: MR imaging features including enhancement and ADC histogram parameters correlate to molecular subgroups in DIPG. Further studies are required to verify and refine these findings in a larger cohort.